How Body Balance Influences Political Party Evaluations: A Wii Balance Board Study - Dijkstra, Katinka; Eerland, Anita; Zijlmans, Josjan; Post, Lysanne (Frontiers in Psychology, 2012)
Embodied cognition research has shown how actions or body positions may affect cognitive processes, such as autobiographical memory retrieval or judgments. The present study examined the role of body balance (to the left or the right) in participants on their attributions to political parties. Participants thought they stood upright on a Wii™ Balance Board, while they were actually slightly tilted to the left or the right. Participants then ascribed fairly general political statements to one of ten political parties that are represented in the Dutch House of Representatives. Results showed a significant interaction of congruent leaning direction with left- or right wing party attribution. When the same analyses were performed with the political parties being divided into affiliations to the right, center, and left based on participants’ personal opinions rather than a ruling classification, no effects were found. The study provides evidence that conceptual metaphors are activated by manipulating body balance implicitly. Moreover, people’s judgments may be colored by seemingly trivial circumstances such as standing slightly out of balance.